2013
DOI: 10.1182/blood-2013-04-490599
|View full text |Cite
|
Sign up to set email alerts
|

Proplatelet generation in the mouse requires PKCε-dependent RhoA inhibition

Abstract: • PKCe, regulating RhoA activity, is a critical mediator of proplatelet formation. • PKCe shut down results inRhoA expression levels that are incompatible with normal platelet generation.During thrombopoiesis, megakaroycytes undergo extensive cytoskeletal remodeling to form proplatelet extensions that eventually produce mature platelets. Proplatelet formation is a tightly orchestrated process that depends on dynamic regulation of both tubulin reorganization and Rho-associated, coiled-coil containing protein ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
3
27
1
Order By: Relevance
“…These effects led to the rearrangement of the actin and microtublin cytoskeletons, which was a known key determinant for PPF, platelet formation, and platelet release. 25,37 Although both NE and EPI stimulate platelet activation, the underlying mechanism is unclear. Here, we discovered that NEand EPI-induced platelet activation was at least partially attributed to ERK1/2 signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects led to the rearrangement of the actin and microtublin cytoskeletons, which was a known key determinant for PPF, platelet formation, and platelet release. 25,37 Although both NE and EPI stimulate platelet activation, the underlying mechanism is unclear. Here, we discovered that NEand EPI-induced platelet activation was at least partially attributed to ERK1/2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…To uncover the underlying mechanisms, we investigated the influences of NE and EPI on the activity of RhoA GTPase, which was reported to regulate the rearrangement of the MK cytoskeleton during PPF. 25,26 Both the NE and EPI treatments led to a significant increase in the Ser188 phosphorylation of RhoA ( Figure 6D-E). Ser188 phosphorylation negatively regulates the activity of RhoA 27,28 ; thus, our results indicated that NE and EPI stimulated PPF via the downregulation of RhoA activity.…”
Section: Continual Stress Increases Platelet Counts In Mice Through Smentioning
confidence: 99%
“…RhoA-dependent signaling has been linked to the production of proplatelets (17,18). Therefore, we treated human megakaryocytes with Y27632, a selective inhibitor of the Rho-associated protein kinase p160ROCK, or with C3 transferase, a direct RhoA inhibitor.…”
Section: Pharmacologic Inhibition Of the Proteasome Blocks Platelet Pmentioning
confidence: 99%
“…32 Furthermore, Kostyak and colleagues have shown that, in a mouse model, PKCδ down-regulation reinforces MK differentiation and platelet production. 34 Since it is well documented that PKCε and PKCδ have opposite expression and function in mouse versus human platelets, 43 we hypothesized that high levels of PKCδ are necessary for adequate human MK differentiation and platelet release.…”
Section: Pkcδ Down-regulation Impairs Mk Differentiation and Plateletmentioning
confidence: 99%
“…[28][29][30] We previously demonstrated that PKCε has a key role in human megakaryocytopoiesis in vitro 27,31 and platelet function in vivo, 3 as well as in proPLT production in the murine model. 32 Specifically, PKCε levels increase in the early phase of in vitro human megakaryocytic (MK) differentiation and decrease in the late phase before platelets release, 31 and a forced PKCε overexpression prevents MK full maturation, 31 while its down-regulation increases MK differentiation. 33 Additionally, more recently we have demonstrated that primary MK from myelofibrotic (PMF) patients express higher levels of PKCε than those from healthy donors (HD), and that PKCε inhibition in PMF restores a bona fide normal MK differentiation.…”
Section: Introductionmentioning
confidence: 99%